Biblical Gardens and the Resilience of Cultural Landscapes—A Case Study of Gdańsk, Poland - Monika Trojanowska (Land, 2022)
In recent years, several biblical gardens were constructed in the harsh climate of Poland. They try to convey spiritual values through the medium of garden art and design. Rarely are they built from scratch with a granted budget; the majority of them represent the effort to revitalize degraded urban space and cultural heritage. In most cases, they are constructed and maintained as a challenge by groups of enthusiasts with no institutional financial help. From the very beginning, they are attracting numerous visitors, individuals, and organized groups to previously neglected spaces. The scope of this paper is to present the phenomenon of their construction, discuss the selected case studies, and try to identify whether their creation is strengthening the resilience of cultural landscapes.